Modular protein-RNA interactions regulating mRNA metabolism: a role for NMR - Cukier, Cyprian D. (Springer-Verlag, 2011)
Here we review the role played by transient interactions between multi-functional proteins and their RNA targets in the regulation of mRNA metabolism, and we describe the important function of NMR spectroscopy in the study of these systems. We place emphasis on a general approach for the study of different features of modular multi-domain recognition that uses well-established NMR techniques and that has provided important advances in the general understanding of post-transcriptional regulation.